A Comparative Study of Low-Income Housing Schemes in Festac Village and Amuwo Odofin Housing Estate: An Approach to Mass Housing. - Idowu, Adetokunbo (Obafemi Awolowo University, 2014)
This study examines the hypotheses that as people are partly involved in construction of housing, their affordability and satisfaction levels are improved. The study is illustrated with two case studies of low-income households in Amuwo Odofin Housing Estate and in Festac Village, both in Lagos State.